Corporate governance and low carbon supply chains: why integrity matters? - Norma, Mohter; Fernando, Yudi (Universiti Malaysia Pahang, 2020)
In this study, we aimed to understand the role of integrity in low carbon supply chain and their benefits towards firm performance and corporate governance. This paper also discussed the important of Board of Director (BoD) in decision making in supply chain. As stakeholders continue to increasingly emphasized integrity practices in their supply chains, the firm should understand and practice the integrity especially involved low carbon supply chain (LCSC) by provided accurate carbon disclosure and report carbon verification and etc,. This is important to shareholder especially Board of Director to make sure the firm performance meet their expectation. By monitoring decision making in low carbon supply chain, the BoD believe can avoid unethical issues such as corruption, manipulation and fraud. Practicing integrity in supply chain, the firm will obtain many advantages in their firm performance. The firm’s performance will increase other than being more trustable and gain competitive advantages from the competitor. The BoD are concern the impact of decision making towards the society. The BoD believe by being integrity in the firm’s management they will meet the society expectation.